2022
DOI: 10.1126/scisignal.abm6265
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA PILA promotes NF-κB signaling in osteoarthritis by stimulating the activity of the protein arginine methyltransferase PRMT1

Abstract: Inflammatory cytokine–induced activation of nuclear factor κB (NF-κB) signaling plays a critical role in the pathogenesis of osteoarthritis (OA). We identified PILA as a long noncoding RNA (lncRNA) that enhances NF-κB signaling and OA. The abundance of PILA was increased in damaged cartilage from patients with OA and in human articular chondrocytes stimulated with the proinflammatory cytokine tumor necrosis factor (TNF). Knockdown of PILA inhibited TNF-induced NF-κB signaling, extracellular matrix catabolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Protein arginine methyltransferase PRMT1 regulated AKT/FOXO1 pathway and enhanced ECM degradation and apoptosis of chondrocytes in joint osteoarthritis (165). The activity of PRMT1 was elevated and controlled osteoarthritis via induction of DHX9 arginine methylation and activation of NF-kB signaling pathway (166). Suppression of PRMT5 reduced MAPK and NF-kB signaling pathway and blocked cartilage degradation in osteoarthritis (167).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Protein arginine methyltransferase PRMT1 regulated AKT/FOXO1 pathway and enhanced ECM degradation and apoptosis of chondrocytes in joint osteoarthritis (165). The activity of PRMT1 was elevated and controlled osteoarthritis via induction of DHX9 arginine methylation and activation of NF-kB signaling pathway (166). Suppression of PRMT5 reduced MAPK and NF-kB signaling pathway and blocked cartilage degradation in osteoarthritis (167).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Conversely, miR-17-5p agomiR had a better protective effect on the surface layer of cartilage and surface erosion was reduced ( Hu et al, 2018 ). Adenovirus-mediated expression of PILA Long non-coding RNA PILA stimulated NF-κB signaling in OA, induing spontaneous cartilage degradation by regulating MMP3, MMP13, and ADAMTS4 in knee joints of DMM-induced mice, thus leading to the degradation of articular cartilage and exacerbating inflammation in osteoarthritis ( Tang et al, 2022b ). Mao et al reported that miR-455-3p expression was decreased while lncRNA HOTTIP and CCL3 were significantly upregulated in OA cartilage tissue and chondrocytes.…”
Section: Regulation Of the Ecm By Lncrnas In Osteoarthritismentioning
confidence: 99%
“…This PDF file includes: Supplementary Materials and Methods Figs. S1 to S12 Tables S1 to S4 references (65)(66)(67)(68)(69)(70)(71)(72)(73) Other Supplementary Material for this manuscript includes the following: data file S1 Mdar reproducibility checklist…”
Section: Supplementary Materialsmentioning
confidence: 99%